IgM against Merozoite Surface Protein 1-Block 2 Haplotypes as New Tools for Plasmodium vivax Infections - Fernanda de Almeida Batalha; Elizangela Farias da Silva; Paula Taquita Serra; Rafaella Oliveira dos Santos; Zeca Manuel Salimo; Yury de Oliveira Chaves; Mirian Ívens Fagundes; Paulo Emílio Feuser; Victor Costa de Souza; Felipe Gomes Naveca; Ricardo A. Machado de Ávila; Paulo Afonso Nogueira (Journal of Global Infectious Diseases)
Introduction: The tools to distinguish relapse from reinfection are needed in malaria-endemic areas. We evaluated seroprevalence against sets of specific peptides to the block 2 region of Plasmodium vivax-merozoite surface protein-1 (PvMSP1) to detect parasite clones. Methods: We applied amplicon deep sequencing (ADS) of block 2 region of the MSP-1 gene (pvmsp1) to determine cocirculating parasite clones within eight P. vivax-infected individuals. Based on this, a seroprevalence of IgM and IgG antibodies against sets of peptides of different block-2 haplotypes was validated. After, we evaluated the seroprevalence in plasma of 72 pregnant women, from which 31 had recurrent P. vivax infections. Results: ADS revealed one block 2 haplotype clone infecting five of eight P. vivax-infected individuals. In all, IgM antibodies, not IgG, recognized only a set of peptides specific to the block 2 haplotype determined by ADS. In the other three patients, ADS determined three concurrent block 2 haplotype clones, among whom there was always one haplotype that predominated with more than 95% of high-quality reads and two other smaller haplotypes with up to 5% and the least was <1%. We observed higher IgM levels against haplotype-specific peptides corresponding to the predominant clone. The seroprevalence of pregnant women showed that anti-haplotype-specific IgM detected coinfection with parasite clones per pregnant woman and we also observed levels of anti-haplotype-specific IgM in primary infection increased in some recurrent episodes. Conclusion: IgM against sets of peptides specific to different pvmsp1 haplotypes may be employed as a serological marker for parasite clones in vivax malaria.